2009
DOI: 10.1177/1742395309104343
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of hope among parents of a child with Duchenne muscular dystrophy: perceiving the human being beyond the illness

Abstract: Previous research has demonstrated that cognitive appraisal plays a central role in psychosocial adaptation to illness. Our research indicates that perception can also shape the nature of hope and suggests that health professionals should pay particular attention to the nature of parental hope. The fabric of parental hope can give an indication of how parents are coping and adjusting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 30 publications
(38 reference statements)
3
74
0
6
Order By: Relevance
“…The optimal time to communicate information about respiratory health in this population appears to be when one discusses etiology and when families indicate that they are ready to hear more. This would be consistent with the research of Samson et al (21), who noted that when it is possible for an individual to take charge of his existence, there is hope.…”
Section: Discussionsupporting
confidence: 91%
“…The optimal time to communicate information about respiratory health in this population appears to be when one discusses etiology and when families indicate that they are ready to hear more. This would be consistent with the research of Samson et al (21), who noted that when it is possible for an individual to take charge of his existence, there is hope.…”
Section: Discussionsupporting
confidence: 91%
“…Bjork et al 26 found that the family's life world fell apart, and they experienced fear, uncertainty, chaos, powerlessness, and loneliness after the diagnosis of acute lymphoblastic leukemia, and parents thought their child would die. Horton and Wallander 27 stated that hope was a resilience factor, and Samson et al 19 reported that it helped parents to absorb the initial crisis of the diagnosis of Duchenne muscular dystrophy.…”
Section: Summary Of the Model: Keeping Hope Possiblementioning
confidence: 98%
“…5,6,9,10 However, survey and interview studies have also described components of DBMD caregiving that were perceived as beneficial, including an improved ability to appreciate life experiences and other positive coping strategies to manage the progressive disease course and chronic sorrow. [12][13][14][15] Pangalila and colleagues' 5 cross-sectional study of parents of adults with DBMD found not only high subjective burden, but also high rating of care as important and rewarding. Kenneson and Bobo 6 found that general life satisfaction was associated with high social support, high resiliency, and high income.…”
Section: Introductionmentioning
confidence: 99%